Time Series Visualization (TSV) of Earthquakes in The Cilacap and Surrounding Earthquake Active Zone using QGIS And USGS Data Set - Agustin, Ninik; Kurniasih, Nani (KH. A. Wahab Hasbullah University, 2023)
Earthquakes in Cilacap often occur with a strength above 5 SR or with a smaller strength. This condition means that earthquake research in the Cilacap area will always be needed. This study aims to display a visualization of the time series of earthquakes in the Cilacap area using QGIS and the USGS dataset. The data set used is the earthquake data set around the Cilacap area from USGS with a time span from 1918 to 2021. The data boundaries of this study are Latitude 7.324˚, Longitude 107.941˚, and Latitude -10.407˚, Longitude 111.116˚. The results of spatial data visualization using the heatmap technique are then analyzed temporally using the Temporal function in the QGIS software. The results of the temporal analysis with frames per year produce 104 frames. Visualization of earthquake data in a time series can show changes in the pattern of earthquake magnitude density and show changes in the geographical location of earthquake points from year to year.